Mediating effect of social anxiety on the association between self-esteem and internet addiction among Chinese vocational school students - Zhu, Yunjiao; Jin, Guifang; Shi, Haiyan; Sun, Chenyu; Wei, Hongyuan; Yang, Linsheng; Hao, Jiahu; Sun, Ying; Su, Puyu; Wu, Xiaoyan; Tang, Xiaowu; Zhang, Zhihua (Frontiers in Public Health, 2025)
IntroductionIn today’s digital age, concerns about internet addiction among adolescents have escalated alongside the widespread use of the internet. Simultaneously, research has spotlighted the influence of psychological factors like self-esteem and social anxiety on addictive behaviors. The aim of this study was to verify the hypothesis regarding social anxiety as a mediator in the association between self-esteem and internet addiction.MethodsA total of 10,158 participants were randomly selected from five vocational schools in Anhui Province, China, with a mean age of 18.5 years. They completed a series of self-administered questionnaires, including the Young Internet Addiction Test (IATS), the Liebowitz Social Anxiety Scale (LSAS), and the Self-Esteem Scale (SES). Structural equation modeling (SEM) was employed to examine the mediating role of social anxiety between self-esteem and internet addiction, adjusting for demographic variables such as age, gender, and parental education.ResultsThe correlation analysis revealed that self-esteem was significantly negatively correlated with internet addiction, while social anxiety was significantly positively correlated with internet addiction. The indirect effect of self-esteem on internet addiction through social anxiety was 0.11 (p < 0.01), constituting 28.35% of the total effect. Additionally, the total impact of self-esteem on internet addiction was 0.278 (p < 0.01). Subgroup analyses by age and gender confirmed the robustness of these findings, with significant total effects observed across different age groups (14–18 years: total effects = 0.637; 18-24 years: total effects = 0.744; p < 0.01) and genders (male: total effects = 0.385; female: total effects = 0.744; p < 0.01).DiscussionThe results indicate that social anxiety plays a significant mediating role in the relationship between self-esteem and internet addiction, affecting both directly and indirectly this association. These findings underscore the importance of addressing self-esteem and social anxiety in interventions aimed at reducing internet addiction among adolescents, suggesting that targeted psychological support could be pivotal in mitigating the risk of developing addictive behaviors online.